USE OF CLOUD PLATFORMS (GOOGLE EARTH ENGINE) IN CARTOGRAPHIC RESEARCH - Винограденко, Сергій (SWorldJournal, 2026)
The article investigates the application of the cloud-based platform Google Earth Engine (GEE) for cartographic research. Modern approaches to satellite data processing are considered, including Landsat 8/9 and Sentinel-2, using scripting tools (JavaScrip